(untitled) (Modern education and development, 2024)
This article examines the impact of depression on education, and more specifically, on learning a foreign language, which is a common problem among young people around the world today. There are several factors that prevent depression from learning a foreign language. Among them, this article analyzes only the cognitive and physiological effects of depression and its consequent impact on the learning performance of young people. В данной статье рассматривается влияние депрессии на образование, а точнее, на изучение иностранного языка, что сегодня является распространенной проблемой среди молодежи во всем мире. Есть несколько факторов, которые мешают депрессии при изучении иностранного языка. Среди них в этой статье анализируются только когнитивные и физиологические эффекты депрессии и ее последующее влияние на успеваемость молодых людей. Bu maqola hozirgi kund butun dunyo miqyosida koʼp uchrayotgan va yoshlar aziyat chekayotgan depressiya kasalligining taʼlim olishga, aniqroq qilib aytganda, biror chet tilini oʼrganishga taʼsirini oʼrganadi. Depressiyaning chet tilini oʼrganishga toʼsqinlik qilayotgan omillari bir nechta. Bu maqola ular orasidan faqat depressiyaning kognitiv va fiziologik taʼsirini va uning natijasida yoshlarning oʼrganish faoliyatiga taʼsirini tahlil qiladi.